Effects of match location, match result and the quality of opposition in training load on a two-matches week in a top-class elite European soccer team - Oliveira, Rafael (2021)
The aim of this study is to analyse effects of match location, match result and level of opponents in training load on the two following days of the match (MD+1; MD+2) in a top-class elite soccer European team. Nine players participated in this study. Total distance covered, distances of different exercise training zones (1–5) and average speed (AvS) were analysed. The session rating of perceived exertion (s-RPE) and Hooper Index scores (fatigue, stress, sleep quality, delayed onset muscle soreness-DOMS) were also analysed. Data was analysedregarding the two following days of a match. All weeks analysed included two matches. The results showed lower values of DOMS, effect size (ES)= 1.69, and fatigue ES=1.25, on the day following an away-win match than a home-defeat match against a bottom level opponent (all, p<0.05). It was also observed higher values of sleep quality ES=1.44, zone 1, ES=-4.35, and AvS, ES=-12.65, but lower values of s-RPE, ES=3.52, on the day following away-win match against a national top-level opponent (TLO). Finally, higher values for zone 3, ES=1.71, and lower value for AvS, ES=-6.06 were observed on the day following away-win match than a home-defeat match against champions league opponent number 1 (all, p<0.05). Total distance, AvS and zone 4 were higher after playing national opponents and/or champions league opponents in MD+1 than MD+2. The pattern of training load seems to be affected by situational variables. In general, the higher the quality of the opponents, the higher Hooper index in MD+1. S-RPE seems to be higher after playing a bottom level opponent when compared with the other opponents. Also, after playing national opponents, total distance, zones 1 and 4 were higher than against international opponents.